2017
DOI: 10.1080/17461391.2017.1282046
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adding a weekly eccentric‐overload training session on strength and athletic performance in team‐handball players

Abstract: To investigate the influence of adding a weekly eccentric-overload training (EOT) session in several athletic performance's tests, 18 team-handball players were assigned either to an EOT (n = 11) or a Control (n = 7) group. Both groups continued to perform the same habitual strength training, but the EOT group added one session/week during a 7-week training programme consisting of four sets of eight repetitions for the bilateral half-squat and unilateral lunge exercises. The test battery included handball thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
97
2
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(123 citation statements)
references
References 40 publications
14
97
2
10
Order By: Relevance
“…Elite handball players achieve significantly higher throwing ball velocities than their lower level counterparts [28,29]-with an 8-9% advantage in elite men [15] and 10-11% advantage in elite females [26]. Hermassi et al [7] and Gorostiaga et al [15] noted an increase in all types of throw ball velocities (standing throw, three-step running throw and jump-throw) following 8 weeks of heavy RT.…”
Section: Throwing Ball Velocitymentioning
confidence: 97%
See 2 more Smart Citations
“…Elite handball players achieve significantly higher throwing ball velocities than their lower level counterparts [28,29]-with an 8-9% advantage in elite men [15] and 10-11% advantage in elite females [26]. Hermassi et al [7] and Gorostiaga et al [15] noted an increase in all types of throw ball velocities (standing throw, three-step running throw and jump-throw) following 8 weeks of heavy RT.…”
Section: Throwing Ball Velocitymentioning
confidence: 97%
“…However, existing studies are mainly focused on concentric exercises [28,29], even though most actions required during handball imply a combination of eccentric and concentric muscular contractions, involving, for example, both concentric and eccentric phases of squat jumps [28,29].…”
Section: Throwing Ball Velocitymentioning
confidence: 99%
See 1 more Smart Citation
“…FIT offers additional resistance throughout the entire ROM via the use of the inertia of a rotating flywheel to provide a greater overall load during coupled concentric and eccentric muscle actions [292]. The use of FIT in adult populations has been reported to provide many benefits including improvements in physiological, physical and performance factors, such as running economy [293], body composition [294], muscle activation [295,296], acute power enhancement [297][298][299][300], muscle architecture [35,[301][302][303][304], change of direction [35,48,305] as well as force-and power-related qualities [25,[305][306][307][308].…”
Section: Flywheel Inertial Trainingmentioning
confidence: 99%
“…In addition, it has been demonstrated that the use of higher flywheel inertias can concomitantly provide eccentric overload via increases of kinetic variables such as negative impulse during the descent phase of a movement [292,327,328]. Therefore, the introduction of low intensity flywheel inertia wheels may represent an appropriate starting point for training progressions along with lower training volumes prior to gradually increasing the load, volume and frequency to that which has been currently reported for FIT in adult populations [25,35,292,302,305] and which reflects current youth resistance training guidelines [17]. Such an approach is provided in Figure 3.…”
Section: Flywheel Inertial Trainingmentioning
confidence: 99%